Does a Duty of Disclosure Foster Special Treatment of Genetic Research Participants?. Issue 5 (17th May 2013) - Hayeems, Robin Z.; Miller, Fiona A.; Bytautas, Jessica P.; Li, Li
Abstract: The principle that research participants not receive enhanced care compared to non‐participants may be challenged by a duty to disclose genetic research results, especially where care is otherwise inaccessible. Autism researchers' attitudes toward providing enhanced care to study participants were analyzed quantitatively using descriptive and multivariate analyses of survey data and qualitatively through thematic analysis of interview data. Approximately half of survey respondents ( n = 168, RR = 44 %) agreed they should provide additional knowledge (52 %) or services (48 %) to study participants that may not be available to non‐participants. Qualitatively ( n = 23), respondents were motivated by the notion of reciprocity but highlighted tensions when research enables access to expertise and therapeutic resources that are otherwise difficult to obtain. For researchers, feeling obliged to report research results may be in conflict with the obligation to avoid special treatment of research participants; this may in turn threaten principles of voluntariness, autonomy, and justice.